Insights from CPTu and Seismic Cone Penetration Testing in the Kathmandu Valley, Nepal - Gilder, Charlotte E. L.; Pokhrel, Rama Mohan; De Luca, Flavia; Vardanega, Paul J. (Frontiers in Built Environment, 2021)
Seismic hazard assessment often relies on static piezocone penetration tests (CPTu) to estimate the Cyclic Resistance Ratio (CRR) and for the evaluation of in situ soil behaviour. This paper presents CPTu data acquired in the Kathmandu valley sediments and makes use of established CPTu interpretation procedures to assess the soil in situ properties. To this point, SPT data and limited shear wave velocity measurements have been predominant for studying the variability and seismic response of soil deposits underlying Kathmandu. This paper provides (a) additional data to add to the existing SAFER/GEO-591 database, (b) new shear-wave velocity measurements and (c) initial estimates of CRR at the sites visited. Based on the work presented in this paper, it is concluded for the Kathmandu valley, a more detailed methodology for liquefaction assessment is needed mainly due to the presence of saturated silts.